STRATEGIC OUTSOURCING IN PHARMACEUTICAL INDUSTRY - Kikerkov, Igor; Slaninka miceska, Maja; Pavlovska, Kristina; Arsovska, Anita (My University, 2022)
The pharmaceutical industry is facing a tremendous challenge from the current global economic crisis. Enormous earnings from new “blockbuster” drugs are perishing and old drug targets are leading to limited profits. Despite substantial investment in research and development of new drugs, the return thereof is disappointing. New targets including biologic, biomarker, as well as studies of the genome, as well of drugs for treatment of chronic diseases, have much longer duration of the development phase. Therefore, companies are focused on shortening duration, lowering costs, enhancing efficiency and minimizing usage of resources. All these challenges are forcing the pharmaceutical industry to change its drug development model from a model relying on internal capacities to an open model that embodies aid from a Contract Research Organization (CRO) experienced in understanding regulatory standards, equipped with adequate infrastructure, qualified and competent staff in pharmacy, and experienced in dealing with regional issues. Outsourcing has great importance for pharmaceutical companies. Manufacturers of original pharmaceuticals may opt for outsourcing of different phases of drug development, while generic companies confide the clinical trial – the last phase of drug development – to selected CROs which meet high standards of expertise in performing the studies, using highly reliable analytical methods, located in attractive geographic locations and have competitive pricing. This paper is inspired by the challenges with which the pharmaceutical industry has to cope in the new globalized world. At the beginning the authors provide short introduction to the significance of outsourcing in the case of the pharmaceutical industry; than differentiate Big Pharma from generic pharmaceutical companies; define benefits and risks from outsourcing in the pharmaceutical industry; stress the significance of project management as a key prerequisite of planned and executed outsourced activities; and finally present concluding remarks.
Keywords: pharmaceutical industry; outsourcing; Contract Research Organization (CRO); Big Pharma; generic companies; project management; drug development